Preterm Hypoxic–Ischemic Encephalopathy - Gopagondanahalli, Krishna Revanna; Li, Jingang; Fahey, Michael C.; Hunt, Rod W.; Jenkin, Graham; Miller, Suzanne L.; Malhotra, Atul (Frontiers in Pediatrics, 2016)
Hypoxic ischemic encephalopathy (HIE) is a recognizable and defined clinical syndrome in term infants that results from a severe or prolonged hypoxic ischemic episode before or during birth. However, in the preterm infant, defining hypoxic ischemic injury, its clinical course, monitoring and outcomes remains complex. Few studies examine preterm HIE, and these are heterogeneous, with variable inclusion criteria and outcomes reported. We examine the available evidence that implies that the incidence of hypoxic ischemic insult in preterm infants is probably higher than recognized, and follows a more complex clinical course, with higher rates of adverse neurological outcomes, compared to term infants. This review aims to elucidate the causes and consequences of preterm hypoxia ischemia, the subsequent clinical encephalopathy syndrome, diagnostic tools and outcomes. Finally, we suggest a uniform definition for preterm HIE that may help in identifying infants most at risk of adverse outcomes and amenable to neuroprotective therapies.